Analysis of Non-Relativistic Energy, Wave Function, and Black Hole’s Application with Minimal Length - A Suparmi; Briant Sabathino Harya Wibawa; C Cari; Suci Faniandari (UNIVERISTAS PGRI MADIUN, 2021)
The Schrödinger equation for q-deformed modified Eckart potential was investigated in the presence of minimal length formalism using the approximate new wave function and q-deformed potential. It was reduced to Schrödinger equation with modified Poschl-Teller potential. This equation was solved using Asymptotic Iteration Method (AIM) to get the energy eigenvalues equation and wave functions. The wave function was used to determined the Rényi entropy of quantum system. Then, the Rényi entropy was used to determine the mass energy parameter, temperature and heat capacity of the black hole for some diatomic molecules. The energy spectra showed that the increase of radial and angular quantum number, potential width, minimal length parameter, and the molecule mass caused the decrease of energy eigenvalues. The radial quantum number and the parameter had the most effect to the wave functions, the number of waves, and the wavelength. The potential width, radial quantum number, and entropy parameter had the most effect on Rényi entropy, mass energy parameter, temperature and heat capacity of Schwarzschild black hole. The increase of quantum number caused the decrease of Renyi entropy, mass energy parameter, temperature and heat capacity of Schwarzchild black hole, but the increase of d caused the increase of Renyi entropy, mass energy parameter, temperature and heat capacity of Schwarzchild black hole.